Modular total synthesis of aculeatins A, B, E, F and 6-epi-aculeatins E, F - Ramana, C. V.; Pandey, Sunil Kumar (Tetrahedron, 2010)
The total synthesis of aculeatins A, B. E and F confirming the assigned absolute configuration of recently isolated aculeatins E and F is documented. A convergent approach has been designed by the addition of both the terminal units (phenol and side chain) at an advanced stage. The central 1,3,5-triol unit with the requisite stereochemistry was prepared from the commercially available alpha-D-glucoheptonic-gamma-lactone. Selective O-debenzylation during the hydrogenolysis of the diyne intermediate and the one pot phenolic oxidation with concomitant spiroketalization highlight the accomplished total syntheses. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: aculeatins; Alkyne-oxirane coupling; Natural products synthesis; Oxidative spiroketalization; Sonogashira coupling

Synthesis of aculeatins A and B via iterative hydrolytic kinetic resolution - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A simple and concise approach for the synthesis of aculeatins A and B starting from (+/-)-epichlorohydrin is described. The synthetic strategy features Jacobsen's hydrolytic kinetic resolution and a Linchpin coupling as key steps.
Keywords: aculeatins; Epoxide; Hydrolytic kinetic resolution; Linchpin coupling; spirocyclization